Implementação por sistemas embarcados de protótipo parametrizável para coleta de dados microclimáticos georreferenciados - Pereira, Roberto Benedito de Oliveira (2013)
This research investigates the use of embedded systems for collecting and storing data microclimate. The aim of this study was to develop a set of hardware and software for the collection, storage and monitoring transects micrometorologics. The locus of the research was the Federal University of Mato Grosso (UFMT). Regarding the delimitation of space/time, this research took place in March 2013. In usability testing of the data acquisition system performed a case study in the area of environmental comfort on the trail walking UFMT for this, we performed a calibration of the equipment through a paired analysis of variance and then we collected the temperature and relative humidity in three heights, and the geographic coordinates that route. After collecting and analyzing data , there were the necessary corrections in the values obtained by each sensor and then generated a semivariogram isotropic temperature and relative humidity , both resulted in an exponential model with a coefficient of determination 76.6 % (Co = 0.2220 , C = 1.1360 + Co , Ao = 612.00 ; r2 = 0.766 ; RSS = 0.133 ) and 78.4 % (Co = 1.2900 , C = 5.6180 + Co , Ao = 347.00 ; r2 = 0.784 ; RSS = 2.25 ), respectively. Generated was also a contoured map by kriging data. During testing of autonomous power, the kit assembled without the bluetooth module, we obtained an average consumption in the standby mode is 57.45 mA and 74.87 mA for recording, with bluetooth module values were respectively 81.27 mA and 106.98 mA. The use of the memory card to set up the equipment and to retrieve stored data proved efficient. Based on the results, we confirm the efficiency of the equipment, the methodology used and the standard Arduino for prototyping.